2001
DOI: 10.1046/j.1464-410x.2001.02274.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment levels of urinary deoxypyridinoline as a potential marker in patients with prostate cancer with or without bone metastasis

Abstract: Objective To assess the predictive role of the bone markers alkaline phosphatase (ALP) and urinary deoxypyridinoline (DPD), as indicators of bone turnover, at baseline in patients with prostate cancer. Patients, subjects and methods Urinary DPD, serum ALP and prostate-speci®c antigen (PSA) were evaluated in 23 patients with benign prostatic hyperplasia (BPH), 115 with prostatic carcinoma, of whom 21 had bone metastasis, and in 16 age-matched control subjects. Results Patients with newly diagnosed prostate canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
1
8
0
3
Order By: Relevance
“…Osteoblastic bone metastases in prostate cancer appear on plain radiographs as areas of increased density (osteodense lesions) and on bone scans as hot spots of increased bone formation 1. In addition, serum bone alkaline phosphatase levels2, 3 and iliac bone histomorphometry4–6 studies have confirmed that bone formation is increased in the tumor-involved sites. However, although these are osteoblastic lesions, the bone that is produced in response to the tumor cells may be fragile and abnormal.…”
Section: Introductionmentioning
confidence: 91%
“…Osteoblastic bone metastases in prostate cancer appear on plain radiographs as areas of increased density (osteodense lesions) and on bone scans as hot spots of increased bone formation 1. In addition, serum bone alkaline phosphatase levels2, 3 and iliac bone histomorphometry4–6 studies have confirmed that bone formation is increased in the tumor-involved sites. However, although these are osteoblastic lesions, the bone that is produced in response to the tumor cells may be fragile and abnormal.…”
Section: Introductionmentioning
confidence: 91%
“…Type I collagen is the major extracellular matrix component of bone, and there is an extensive body of evidence that type I collagen breakdown products, including NTx, are present at elevated levels in the serum and urine of patients with CaP bone metastases. (1)(2)(3)(47)(48)(49) Increased resorption associated with bone metastases, including CaP bone metastases, is linked to stimulation of osteoclastogenesis through RANKL expression. (8 -10) Augmented NTx levels are generally associated with increased osteoclastic bone resorption activity because of cat K expressed by these cells, yet we observed osteoclasts in samples from only 3/14 patients with advanced CaP bone metastases.…”
Section: Cathepsin K In Prostate Cancermentioning
confidence: 99%
“…Although most CaP bone metastases are considered osteoblastic, based on patterns observed on radiographs, there is evidence that markers of bone resorption are elevated in patients with CaP bone lesions. (1)(2)(3) Detailed studies of bone metastases using histomorphometry have also demonstrated that radiographically sclerotic lesions exhibit both bone formation and resorption. (4 -7) Recently it has been established that various cancers, including breast and prostate, support osteoclastogenesis through expression of the receptor activator of NF-kB ligand (RANKL), (8 -10) providing one possible mechanism to explain the increased bone resorption observed with bone metastases.…”
Section: Introductionmentioning
confidence: 99%
“… 15 ). In patients with prostate cancer, the combined measurement of PSA and BAP in serum seems to increase the diagnostic sensitivity for bone lesions compared to healthy subjects or patients with benign prostate hyperplasia 16–18 …”
Section: Diagnostic Usementioning
confidence: 99%
“…In patients with prostate cancer, the combined measurement of PSA and BAP in serum seems to increase the diagnostic sensitivity for bone lesions compared to healthy subjects or patients with benign prostate hyperplasia. [16][17][18] In general, serum osteocalcin (OC) levels are more variable compared to other bone formation markers, and in advanced, untreated metastatic bone disease, serum OC levels may be low in the presence of high BAP levels. 19 The reasons for this dissociation are unclear, but possibilities include proteolytic cleavage of OC, changes in gene expression or disturbed osteoid maturation in the presence of active tumour osteopathy.…”
Section: Diagnostic Usementioning
confidence: 99%